Classical 18.5-and 21.5-kDa Isoforms of Myelin Basic Protein Inhibit Calcium Influx Into Oligodendroglial Cells, in Contrast to Golli Isoforms - Smith, Graham S.T. (2011)
The myelin basic protein (MBP) family arises from different transcription start sites of the golli (gene of oligodendrocyte lineage) complex, with further variety generated by differential splicing. The “classical” MBP isoforms are peripheral membrane proteins that facilitate compaction of the mature myelin sheath but also have multiple protein interactions. The early developmental golli isoforms have previously been shown to promote process extension and enhance Ca(2+) influx into primary and immortalized oligodendrocyte cell lines. Here, we have performed similar studies with the classical 18.5- and 21.5-kDa isoforms of MBP. In contrast to golli proteins, overexpression of classical MBP isoforms significantly reduces Ca(2+) influx in the oligodendrocyte cell line N19 as well as in primary cultures of oligodendroglial progenitor cells. Pharmacological experiments demonstrate that this effect is mediated by voltage-operated Ca(2+) channels (VOCCs) and not by ligand-gated Ca(2+) channels or Ca(2+) release from intracellular stores. The pseudo-deiminated 18.5-kDa and the full-length 21.5-kDa isoforms do not reduce Ca(2+) influx as much as the unmodified 18.5-kDa isoform. However, more efficient membrane localization (of overexpressed, pseudo-deiminated 18.5-kDa and 21.5-kDa isoforms of classical MBP containing the 21-nt 3′-untranslated region transit signal) further reduces the Ca(2+) response after plasma membrane depolarization, suggesting that binding of classical MBP isoforms to the plasma membrane is important for modulation of Ca(2+) homeostasis. Furthermore, we have found that the mature 18.5-kDa isoform expressed in oligodendrocytes colocalizes with VOCCs, particularly at the leading edge of extending membrane processes. In summary, our findings suggest a key role for classical MBP proteins in regulating voltage-gated Ca(2+) channels at the plasma membrane of oligodendroglial cells and thus also in regulation of multiple developmental stages in this cell lineage.